Factors Influencing Willingness To Contribute In Cash Waqf: Case Of South Tangerang, Indonesia - Ahmad Hudzaifah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
Waqf has long been the backbone of community service in Indonesia, especially in the fields of religion and education. Considering the importance of waqf in the socio-economic field in Indonesia, the government expanded the scope of waqf which was originally only in the form of fixed assets and then added with movable assets such as money. As a country with the largest Muslim population in the world, Indonesia has a huge cash waqf potential. But this potential has not been able to be optimized by the government or the private sector. The problem of the lack of awareness of Muslims in Indonesia about cash waqf is the main obstacle. There are several factors that influence one's willingness to do cash waqf, namely knowledge, income, social culture, and promotion. To determine the influence of these factors, the data obtained from respondents from the survey instrument adopted were subjected to descriptive analysis statistical analysis. The findings indicate that all factors significantly affect a person's willingness to do cash waqf. Recommendations contingent on research findings were offered